Analysis of wearing masks compliance during the COVID-19 pandemic based on the Health Belief Model - Dhandi Wijaya; Misnaniarti Misnaniarti; Rico Januar Sitorus (Public Health of Indonesia)
Background: Maintaining physical distance, washing hands, and wearing masks during the COVID-19 pandemic are very important in preventing the spread of the virus. However, although the use of facemasks is relatively easy to do, its compliance is considered low.